CO-PYROLYSIS OF SCRAP TIRES (ST) DAN PLASTIK POLYPROPYLENE (PP): DISTRIBUSI PRODUK DAN PROPERTIS FISIK PYRO-OIL - Ilyas Sofana; Widya Wijayanti; Nurkholis Hamidi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Plastic waste and scrap tires (ST) have now become pollution that harms the environment in various cities around the world if not managed properly. As pollutants, the two types of waste are actually very interesting to manage because they contain hydrocarbon elements so that they can be processed and have the potential to become alternative fuels. This study aims to determine the effect of co-pyrolysis of scrap tires (ST) and polypropylene (PP) plastic on the distribution of products in the form of oil and char/charcoal. The pyrolysis process was carried out at a temperature of 450℃ for 90 minutes using a fixed bed pyrolysis reactor with ST:PP mixing variations, namely 9:1, 8:2, 7:3, 6:4, and 5:5. The maximum pyrolysis product yield in the form of oil as much as 40.7 Wt% was obtained at a 6:4 mixing variation followed by a 7:3 (36.7 Wt%) mixing variation, then a 5:5 variant (36 Wt%), after that an 8:2 variant (34.3 Wt%) and the last is the 9:1 mixing variation with a total of 28.3 Wt%. For the maximum pyrolysis product in the form of char as much as 42.6 Wt% obtained at 9:1 mixing variation followed by 7:3 mixing variation (41 Wt%) after that 8:2 variant with 38.7 Wt%, then 6:4 with the amount of 27.7 Wt%, and the last is the mixing variation of 5:5 to obtain the char result of 18.3 Wt%. Physical properties of pyro-oil in the form of density and calorific value will also be shown in this study.